Synthesis of aluminum nitride thin film using reactive RF-magnetron sputtering - Semblante, Oliver D.; Somintac, Armando S. (Quezon City Materials Science and Engineering Program, College of Science, University of the Philippines Diliman, 2010)
Aluminum nitride (AIN) thin films were grown using reactive rf-magnetron sputtering with a sputtering gas composed of argon and nitrogen mixture at a partial pressure ratio of 1:3. Films were grown at 70W of rf-power without application of substrate heating from an external source. The deposited films were crack free and non-porous but were amorphous in nature as verified through SEM and XRD studies respectively.
Thesis (Master of Science in Materials Science and Engineering)--University of the Philippines Diliman
Keywords: Aluminum nitride; Thin films